2002
DOI: 10.1039/b109150f
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of osmium thin films using pyrazolate complexes as CVD source reagents

Abstract: The reaction of Os 3 (CO) 12 with 1.2 eq. of pyrazole (3,5-(CF 3 ) 2 -pz)H at 190 uC affords triosmium complex Os 3 (CO) 10 (3,5-(CF 3 ) 2 -pz)(m-H) (1) as the isolable product. Upon further treatment with excess pyrazole (3,5-(CF 3 ) 2 -pz)H under more forcing conditions, complex 1 converts to a diosmium pyrazolate complex [Os(CO) 3 (3,5-(CF 3 ) 2 -pz)] 2 (2) in high yield. These osmium complexes are characterized by spectroscopic methods and single crystal X-ray diffraction study, showing the expected triang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Among them, are the well-known wet chemical methods, chemical vapor deposition (CVD), electro deposition and pulsed laser deposition (PLD) in recent years. [14][15][16] There are few reports for the fruitful preparation of Os NPs with different sizes and morphologies such as nano-wires, 17 nano-clusters, 18 wire-like aggregates in an organic-aqueous hybrid medium 19 and thin lms. 15 Krämer et al prepared iron, ruthenium, and osmium NPs using a metal carbonyl precursor as starting material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, are the well-known wet chemical methods, chemical vapor deposition (CVD), electro deposition and pulsed laser deposition (PLD) in recent years. [14][15][16] There are few reports for the fruitful preparation of Os NPs with different sizes and morphologies such as nano-wires, 17 nano-clusters, 18 wire-like aggregates in an organic-aqueous hybrid medium 19 and thin lms. 15 Krämer et al prepared iron, ruthenium, and osmium NPs using a metal carbonyl precursor as starting material.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] There are few reports for the fruitful preparation of Os NPs with different sizes and morphologies such as nano-wires, 17 nano-clusters, 18 wire-like aggregates in an organic-aqueous hybrid medium 19 and thin lms. 15 Krämer et al prepared iron, ruthenium, and osmium NPs using a metal carbonyl precursor as starting material. 12 Os thin lm was fabricated from osmacene at higher temperature by atomic layer deposition technique.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of various properties of Os and its oxides, Os metal is a demanding material to manufacture and work with. Different types of routes have been employed for the formation of Os NPs mostly in thin film form, for example, chemical vapor deposition (CVD), physical vapor deposition (PVD), electrodeposition, vacuum pyrolysis, and sol–gel techniques. Os metal generally alloys with other materials like Os doped SnO 2 used as a sensor and Os–Pd NPs used in catalytic reactions. , Different types of biomolecules like amino acids, peptides, and protein have been used as a template and as a stabilizing agent during NPs synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the same reaction product can be isolated in comparable yield via heating of a hexane solution of Ru 3 (CO) 12 and (dmpz)H in a stainless steel autoclave (170 °C, 24 h). In this case, the reaction conditions are akin to those used for the synthesis of the diosmium pyrazolate complex [Os 2 (CO) 6 (hfpz) 2 ], hfpz = 3,5-bis(trifluoromethyl)pyrazolate, described in the literature . Interestingly, both the literature report and our experimental observation have revealed that complex 1a does not lose CO even at elevated temperature and under vacuum.…”
Section: Resultsmentioning
confidence: 87%